THE HOBBESIAN TURN - Margolis, Joseph (The Nordic Journal of Aesthetics, 2018)
The “Hobbesian turn” is an invention out of whole cloth, a device by which to oppose the usually supposed autonomy of the aesthetic, the moral, the political, and the factual; to recover the collective holism of civilizational (or enlanguaged cultural) life; to feature the existential historicity of the human career, which is incompatible with any strict universalism and all the forms of transcendentalism; hence, also, to feature the adequacy of a contingent Lebensform in collecting the affinities of creative expression and agentive commitment within the terms of human solidarity; to abandon strict universality and necessary synthetic truths; and to favour the fluxive world of pragmatist construction rather than the indemonstrable fixities of rationalism and transcendentalism. The article proceeds largely by examining aspects of Picasso’s career and the history of Western politics spanning the sixteenth century to the present.